On Certain Classes of p-Valent Functions by Using Complex-Order and Differential Subordination - Abdolreza Tehranchi; Adem Kılıçman (International Journal of Mathematics and Mathematical Sciences)
The aim of the present paper is to study the p-valent analytic functions in the unit disk and satisfy the differential subordinations z(Ip(r,λ)f(z))(j+1)/(p-j)(Ip(r,λ)f(z))(j)≺(a+(aB+(A-B)β)z)/a(1+Bz), where Ip(r,λ) is an operator defined by Sălăgean and β is a complex number. Further we define a new related integral operator and also study the Fekete-Szego problem by proving some interesting properties.